In vivo neutron activation study of the short-term kinetic behaviour of sodium and chlorine in the human hand. (6th October 2016) - Mohseni, H K; Cowan, D; Chettle, D R; Priest, N D; Atanackovic, J; Byun, S H; Prestwich, W V
Abstract: The time-dependent behaviour of sodium and chlorine was studied as a spinoff from a study of aluminum in the hand of subjects suffering from Alzheimer's disease and a control group, involving 15 Alzheimer's and 16 control subjects with an age range of 63–89 years. This was achieved using the in vivo neutron activation analysis system developed at McMaster University for the non-invasive measurement of aluminum, where a subject's hand is placed in a beam of accelerator-based thermalized neutrons, which activates elements by neutron capture. Following irradiation, the subject's hand is placed in a detection system comprising 9 NaI(Tl) detectors arranged in a 4π geometry to measure activated elements. The redistribution half-lives of the activation products 24 Na and 38 Cl from the hand were determined after correction for the physical half-life, by means of sequential analysis of the residual activity in the hand. The kinetic behaviours of sodium and chlorine were best characterized by an exponential function corresponding to the rapidly exchangeable pool. The mean redistribution half-lives from the hand for sodium and chlorine in the control subjects were 40.5  ±  17.4 min and 24.2  ±  8.5 min, respectively. For Alzheimer's disease subjects the mean redistribution half-lives were 58.2  ±  36.1 min for sodium and 33.6  ±  16.7 min for chlorine. There was no significant difference in chlorine and sodium redistribution half-lives between the Alzheimer's disease and control group subjects. These results are promising, given that the irradiation and counting protocol were optimized for the aluminum study, rendering them suboptimal for analyzing other elements and their rate of change with time. Further improvements include optimizing the irradiation protocol, longer counting times, and measuring the activity in the un-irradiated hand in various time intervals following irradiation.